A trajetória histórica do movimento docente de Minas Gerais: da UTE ao Sind-UTE - Wellington de Oliveira (2006)
Ahead of the occured changes in the world of the work, mainly from years 80, one became significant to inside study the behavior of the union movement of this context. My specific concern falls again on the movement of the workers of the education of Minas Gerais, justifying it in virtue of my professional and unionist performance in the related movement. The cited movement had an important during the end of years 1970, when "New Unionism" is inserted in the context of the call. Ahead of these comments and, in elapsing of the years I could, also, to evidence that the movement, in that it says respect to the used speech to motivate the set of the workers similar of whom they can engage in the fights, apparently it remains the same, as well as the strategies, or either, assemblies, meetings of representatives and until the extreme resource of the movements strikers. As empirical comments, this behavior of the union movement more is taken root in the workers of the education of the public service, where the resource of the strike is used with more frequency. However, what it intrigues me is the unionism practical permanence of one practically static one, exactly ahead of diverse in the different historic moments that seem to be taking to the faraway of the union front to its bases, mainly because, keeping the strategies and the language, the results of the more negative movements are each time, as much in that it says respect to the economic claims, as well as in the plan of the organization politics of the movement. Therefore, the strikes in the public nets in Minas Gerais, economic results are happening almost that annually and politicians are not being positive, therefore it urges to study them and to make an analysis of them, mainly when one verifies the persistence and the insistence in the strategy. The chronological cut contemplating in this article will look for to reflect the development of the movement of the workers of the education in Minas Gerais, or either, I will investigate from the end of decade of 70 until the beginning of century XXI. This is justified cut in function of that it is from the decade of 70, after a movement striker, that the Union of the Workers of the Education of a context of crisis of the military dictatorship in Brazil is created inside. Also it is stranded out that the denomination "Workers of Education" is an innovation inside of a movement of professors. If it does not have to forget that the movement of professors is inaugurated in Brazil with the strikes of the Bahia and Paraná in 1978, being that one year later, 18 of May of 1979, the mining professors carry through a strike that lasted 41 days and reaching 420 cities. From there my analytical starting point. Extending the posterior decades to it, I will look for to establish comparative parameters so that if the reason of permanence cans revelator related practical changes of the syndical ones already in the body of this proposal of work. My work inserts, therefore, in the analytical perspective of the social movements that unclasp in the end of the decade of 70, in this context it self with the "New Unionism" and as Eder SADER would say, the "New Authors" who get inside the social scene in Brazilian politics. They had pointed in the direction of one politics consisting from the questions of the daily life. They had pointed with respect to a new conception of politics, from the direct intervention of the interested parties. They had placed the claim of the cited democracy to the spheres of the social life: in the plants, in the unions, in the public services and the administrations in the quarters. (SADER, 1988:313) 1 . Therefore, after the carried through research, either through the harvested interviews, using the techniques of Oral History, in the referring bibliography to the world of the work and, in specific the unionism, in documents produced for analyzed entity (UTE/Sind-UTE) and in the press written in such a way in periodicals of the call the great press as in said periodicals alternative of time, I made a point in the direction that in the historical trajectory of the teaching movement in Minas Gerais will occur a strangeness between the leading nucleus /social base.